A CBCT study of the gravity-induced movement in rotating rabbits. (16th May 2018) - Barber, Jeffrey; Shieh, Chun-Chien; Counter, William; Sykes, Jonathan; Bennett, Peter; Ahern, Verity; Corde, Stéphanie; Heng, Soo-Min; White, Paul; Jackson, Michael; Liu, Paul; Keall, Paul J; et al.
Abstract: Fixed-beam radiotherapy systems with subjects rotating about a longitudinal (horizontal) axis are subject to gravity-induced motion. Limited reports on the degree of this motion, and any deformation, has been reported previously. The purpose of this study is to quantify the degree of anatomical motion caused by rotating a subject around a longitudinal axis, using cone-beam CT (CBCT). In the current study, a purpose-made longitudinal rotating was aligned to a Varian TrueBeam kV imaging system. CBCT images of three live rabbits were acquired at fixed rotational offsets of the cradle. Rigid and deformable image registrations back to the original position were used to quantify the motion experienced by the subjects under rotation. In the rotation offset CBCTs, the mean magnitude of rigid translations was 5.7  ±  2.7 mm across all rabbits and all rotations. The translation motion was reproducible between multiple rotations within 2.1 mm, 1.1 mm, and 2.8 mm difference for rabbit 1, 2, and 3, respectively. The magnitude of the mean and absolute maximum deformation vectors were 0.2  ±  0.1 mm and 5.4  ±  2.0 mm respectively, indicating small residual deformations after rigid registration. In the non-rotated rabbit 4DCBCT, respiratory diaphragm motion up to 5 mm was observed, and the variation in respiratory motion as measured from a series of 4DCBCT scans acquired at each rotation position was small. The principle motion of the rotated subjects was rigid translational motion. The deformation of the anatomy under rotation was found to be similar in scale to normal respiratory motion. This indicates imaging and treatment of rotated subjects with fixed-beam systems can use rigid registration as the primary mode of motion estimation. While the scaling of deformation from rabbits to humans is uncertain, these proof-of-principle results indicate promise for fixed-beam treatment systems.